Akuntansi Manajemen Syariah dan Konstruksi Sosial (Sebuah Studi Literatur) - Aziz, Fathul Aminudin (AKTSAR: Jurnal Akuntansi Syariah, 2019)
In the reality of life, management accounting has many variables related to social aspects through the basic assumptions of behavior by looking at the Islamic world. The purpose of this study is to make a construction of Islamic management accounting with the social aspects of Muslim behavior. This research is literature research. The principle used in this discussion is to "fix old things that are good and make new things that are better". Management accounting should ideally be built and practiced based on social values so that the information transmitted is also social. In the end, economic decisions are taken by top management and middle management based on social assessments that encourage the creation of economic and business realities that lead to prosperity in justice and prosperity.